Genetic structure in the Genista ephedroides complex (Fabaceae) and implications for its present distribution. (3rd March 2015) - De Castro, Olga; Véla, Errol; Vendramin, Giuseppe Giovanni; Gargiulo, Roberta; Caputo, Paolo
Abstract : The present investigation investigated the genetic structure of a monophyletic group of endemic species belonging to the Genista ephedroides species group: G. bocchierii, G. cilentina, G. demarcoi, G. dorycnifolia, G. ephedroides, G. gasparrinii, G. insularis, G. numidica, G. tyrrhena subsp. tyrrhena, G. tyrrhena subsp. pontiana and G. valsecchiae, all distributed in the western Mediterranean. Using seven plastid microsatellites, 16 populations (288 individuals) were screened. Haplotype fixation was observed in particular for most of the Tyrrhenian taxa (i.e. G. bocchierii, G. cilentina, G. demarcoi, G. ephedroides, G. gasparrinii, G. insularis, G. tyrrhena subsp. tyrrhena and G. valsecchiae ). However, although genetic diversity within populations was low [( hS  = 0.132 (± 0.056)], a high level of total plastid DNA diversity [ hT  = 0.866 (± 0.042)] was detected, and analysis of molecular variance indicated that variation is almost exclusively expressed among populations (95.25%). The plastid microsatellites identify two groups of taxa, one including Sardinian taxa and populations of G. tyrrhena subsp. pontiana and the other including two subgroups, one of which includes Sicilian/Aeolian elements and the other with G. numidica / G. cilentina and G. dorycnifolia . Results allow us to consider G. cilentina as originating by recent anthropogenic dispersal and G. tyrrhena subsp. pontiana as a possible stabilized hybrid between local plants and members of the Sardinian group contributing the maternal lineage. The evolutionary history of the group possibly results from the effects of ancient events fostering geodispersal and range contraction, followed by more recent long‐range dispersal or geodispersion over Pleistocenic land bridges. © 2015 The Linnean Society of London, Botanical Journal of the Linnean Society, 2015, 177, 607–618.